Estimation of polycyclic aromatic hydrocarbons (PAHs) emission and its toxicity potentials from the combustion of selected fuelwoods - Ebenezer Leke Odekanle; Royal Oghosasere Taiwo; Jacob Ademola Sonibare; Adenike Omowumi Akinyemi; Timothy Adesoye Adekanye; Bamidele Sunday Fakinle (Case Studies in Chemical and Environmental Engineering)
In many developing nations, wood is still commonly used as a fuel for domestic cooking. However, fuelwood combustion can have a pronounced effect on air quality by releasing considerable level of PAHs, thereby posing serious risk to global and environmental health. In this study, seven fuelwood samples were cut into small pieces (100 g) and subjected to open burning with a view to estimate PAHs emissions and their toxicity potentials. During combustion, sixteen basic PAHs were characterized by collecting gaseous emissions from the combustion on PUFs (Polyurethane foams) using probe from the air sampler. The PUFs were washed in a Soxhlet extractor with Acetone to extract the emission which was then analyzed using Gas Chromatography/Mass Spectrometry for characterization. Chrysene and Dibenzo[a, h]anthracene have the highest and lowest PAHs concentrations, respectively. All PAHs levels observed exceeded permissible limits of 1x10−6 and 1.2x 10−7 mg/m3 of European Union and World Health Organization, respectively. PAHs from cashew wood showed highest levels of toxicity and mutagenicity, while all the samples have the same carcinogenic effect, indicating that all the samples have the same environmental/harmful impacts, going by ∑PAHcarc/∑PAH ratios (ratio that indicates general harmfulness). The study concluded that despite the relatively low toxic, mutagenic and carcinogenic effects observed in this study, exposure to these concentrations for a long period should be avoided, especially for persons with existing known health conditions such as asthma, lung cancer and cardiovascular diseases.